Upaya Pemenuhan Dokter Spesialis Berstatus Aparatur Sipil Negara Di Rumah Sakit Umum Daerah Ditinjau Dari Undang-Undang Nomor 44 Tahun 2009 Tentang Rumah Sakit - Evan Prasetianto (Doktrin:Jurnal Dunia Ilmu Hukum dan Politik, 2023)
of Law No. 23 of 1992 concerning health explained that the notion of health is "a state of well-being of the body, soul and social that allows everyone to live productively socially and economically". Meanwhile, according to Mu'rifah personal health is all efforts and actions of a person to maintain, maintain and improve the degree of his own health within the limits of his ability, in order to get the pleasure of life and have the best workforce. A person's health is not only measured from the physical, mental and social aspects, but also measured from his productivity in the sense of having a job or producing economically. For those who have not yet entered working age, children and adolescents, or for those who are not working (retired) or old age, namely having activities, for example schools or colleges for children and youth, and social service activities for the elderly.